Attitudes of Emergency Nurses and Patients’ Family Members Towards the Presence of Family Members During Cardiopulmonary Resuscitation; a Cross-sectional Study - Hosseini Marznaki, Zohreh; Karkhah, Samad; Mohammadian Amiri , Mehdi; Källmen, Håkan; Moradi, Azadeh; Najjarboura, Maede (Archives of Academic Emergency Medicine, 2022)
Introduction: Family presence during cardiopulmonary resuscitation (CPR) is one of the elements where family-centered care is practiced. This study aimed to investigate the attitudes of Iranian emergency nurses and patients’ family members regarding the presence of family during CPR. Methods: In a cross-sectional study, 350 emergency nurses and 254 family members of patients admitted to the emergency department of an educational hospital in Iran were enrolled. Data were collected from May to November 2020 using convenience sampling and using a 27-item questionnaire of participants' attitudes towards family presence during CPR. Results: The mean attitude scores of nurses and family members of patients regarding family presence during CPR were 86.79 ± 7.50 and 92.48 ± 6.77, respectively (p < 0.001). The highest and lowest mean scores of nurses' attitude towards family presence during CPR were related to "CPR performance will be negatively influenced" and "Family members have the right to be present during CPR of their relatives/ Allows relatives to stay with the patient until the end/ Makes the patient less worried ", respectively. The highest and lowest mean scores of family members’ attitude towards family presence during CPR were related to "Family members may interfere with CPR" and " May be beneficial to the relatives’ grieving process ", respectively. Conclusion: Overall, the results of this study showed that the attitude of emergency nurses and patients’ family members towards family presence during CPR was positive. Of course, the mean attitude score of nurses in this regard was significantly lower.